Methods for the Study of Physical and Chemical Stability and Container-Content Interactions: Report of a GERPAC Workshop - Sautou Valérie; Lagarce Frédéric (De Gruyter, 2019)
This opinion paper describes the discussions of the attendees of the last GERPAC European conference workshop on the question of chemical stability and container-content interactions. Pharmacists discussed the steps to implement to carry out those studies that are particulary important to asses the quality of the compounded preparations in hospital pharmacies.